Integration of Ambulatory Clinical Pharmacy Services in a Gastroenterology Clinic for Management of Hepatitis C Infection: A Pilot Study - Erika Bower; Haley Holtan; George Konstantinides; Shannon Reidt (University of Minnesota Libraries Publishing, 2017)
Purpose: The purpose of this study is to describe implementation of comprehensive medication management (CMM) services in a gastroenterology (GI) clinic for HCV patients on direct acting antivirals (DAAs), and to evaluate services in terms of identification of medication related problems (MRPs), patient satisfaction, and provider satisfaction. Methods: Six months of visit data was retrospectively collected to determine demographic data and to analyze pharmacist's identification of MRPs. Patient satisfaction surveys were collected using a thirteen question validated pharmacist-satisfaction survey. After pilot completion, a twelve-question survey was sent to all GI clinic staff members to evaluate overall staff satisfaction with services. Results: Ninety-four CMM visits were completed. A total of 246 MRPs were identified with an average of 2.6 MRPs per visit. Seventy-eight MRPs were related to appropriate indication, 27 to efficacy, 30 to safety, and 109 to adherence. Forty MRPs were related to drug-drug interactions. Patient satisfaction surveys revealed that 86% of respondents rated the quality of care and services from the clinical pharmacist as "Excellent". Patients better understood and felt confident with therapy. All staff satisfaction survey respondents strongly agreed or agreed that the pharmacist made valuable contributions to the clinic and patient care. All also strongly agreed that pharmacy's CMM services were an essential component to the management of HCV. Conclusion: Data supports continued involvement of clinical pharmacists within the clinic to promote safety and efficacy of DAAs. Patient and staff satisfaction survey results further illustrate the importance and value that CMM provided by clinical pharmacists can provide. Conflict of Interest We declare no conflicts of interest or financial interests that the authors or members of their immediate families have in any product or service discussed in the manuscript, including grants (pending or received), employment, gifts, stock holdings or options, honoraria, consultancies, expert testimony, patents and royalties.   Type: Original Research